Propagação vegetativa de Himatanthus sucuuba (Spruce ex Müll. Arg.) Woodson por meio das técnicas de estaquia e embriogênese somática - Vasconcelos, Rayssa Gomes (Ciências de Florestas Tropicais - CFT, 2020)
Vegetative propagation techniques, such as cutting and somatic embryogenesis, can be an advantageous alternative to the production of native species seedlings with social-environmental and economic importance as Himatanthus sucuuba. In this context, the present study aimed to evaluate the effect of different types of cuttings and indole butyric acid (IBA) concentration, on the survival and rooting of cuttings of H. sucuuba, as well as to induce somatic embryogenesis in callus originating from nodal and foliar segments in different cultivation conditions. In the cuttings, the experimental design used was in randomized complete blocks, with a factorial arrangement: 2 types of cuttings (with and without leaves) and 3 concentrations of IBA (0, 1000 and 3000 mg L–1). After 100 days, were evaluated the following variables: survival (%), rooting (%), number of roots per cutting, length of the largest root (cm), number of leaves and dry biomass. The somatic embryogenesis experiment was subdivided into three distinct phases: induction (I), maturation (II) and germination of somatic embryos (III). In phase I, the explants' responses to callus formation in MS medium, with 2,4-dichlorophenoxyacetic acid (2.4-D) and Thidiazuron (TDZ) (18.08+9.8 μM and 4.52+6.81 μM), were evaluated using descriptive statistics. In phase II, the effects of abscisic acid (ABA) on the formation of embryogenic structures in the callus were evaluated, in MS and B5 medium, with and without the addition of activated carbon. And in phase III, the potential for conversion of embryos to seedlings in B5 medium supplemented with IBA+BAP (6-benzylaminopurine). The design used in the last two phases was completely randomized, with a 2x2x4 and 2x2x2 factorial arrangement, respectively: 2 explants (nodal and leaf segment callus), 2 light conditions (white and dark light), 4 concentrations of ABA (0, 10, 20 and 30 μM) or 2 concentrations of AIB+BAP (1+2.5 μM and 1+5 μM). The data were subjected to analysis of variance (ANOVA) and means compared by Tukey’s test at p<0.05. As for the percentage of survival and rooting of cuttings, average values above 70% were observed in all treatments. There was no significance for the interaction of the factors analyzed, neither for the effect of AIB, analyzed in isolation. The cutting of H. sucuuba was considered viable, and the maintenance of the leaves, associated with juvenility of the propagules, were determining factors in the conditions in which this study was developed. The results obtained for somatic embryogenesis demonstrate a double interaction between the type of explant and the luminosity and absence of significant differences for ABA. Despite the success in callus induction, the following maturation and germination protocols were ineffective for obtaining seedlings using this technique. New studies must be carried out in order to intensify the expression of somatic embryogenesis, bypass the phenolic oxidation of the culture and increase the rooting and survival percentages in the cutting technique.
Keywords: Propagação vegetativa; Embriogênese somática; Estaquia